Fa’āliyyah Ittikhād Manhaj al-Makālamah wa al-Mabāhaṡah fī Tahqīq Ta’allum al-Balāgah bi al-Ma’had - Ika Pramesti; Rina Dian Rahmawati (Aphorisme: Journal of Arabic Language, Literature, and Education, 2022)
The purpose of this study was to test the effectiveness of using the calling and discussion method in improving Balagah's learning abilities. This research is quantitative with demographic analysis, and the subject of the study is all students from the fifth semester. Its model is the students from the fifth B semester with a total of 19 students—data collection by questionnaire, observation, and documentation. Furthermore, they were then analyzed by the "Korelasi Product Moment" formula. Based on it, after it was found from the result of the analysis, there the conclusion is that: (1) The effectiveness of adopting the call and discussion approach is shown in the question data in the index of question 1.4, the fourth number, that before entering the classroom, the teacher gave a brief description of the subject, which is 94.7%. And then the question, the fifth number, that the teacher's explanation of the teaching of the subject is clear, which is 84.2%. Then, in Fahrous 2.4, the fourth pointer question shows that the students follow the discussion well and ask about the lesson, which is 73.6%. (2) The achievement of students' learning shows in the data of the question in the index of question 2.4, the seventh score, that most of the students stick to their first output, and the third of them raises their output, which is 84.2%. Moreover, their product decreases, which is 10, 2%. (3) From calculating the data before that, there is a strong connection between the effectiveness of adopting the curriculum of call and discussion with the investigation, learning rhetoric of the subject "Rulosity for the fifth semester at the modern, programmed, global institute of the academic year 2019-2020, which is 0.977.